Purification, identification and functional characterization of an immunomodulatory protein from Pleurotus eryngii. Issue 7 (13th June 2018) - Hu, Qiuhui; Du, Hengjun; Ma, Gaoxing; Pei, Fei; Ma, Ning; Yuan, Biao; Nakata, Paul A.; Yang, Wenjian
Abstract : Pleurotus eryngii contains bioactive compounds that can activate the immune system. Abstract : Pleurotus eryngii contains bioactive compounds that can activate the immune system. Here we report the identification, purification, and functional characterization of the bioactive P. eryngii protein (PEP) 1b. PEP 1b was discovered to be a 21.9 kDa protein with the ability to induce the M1-polarization of the macrophage cell line RAW 264.7 cells. Biochemical measurements showed that PEP 1b stimulated nitric oxide (NO), IL-1β, IL-6 and TNF-α production and regulated inducible NO synthase. Phosphorylation and inhibitor studies revealed that PEP 1b promoted the translocation of NF-kB from the cytosol to the nucleus allowing the induction of target gene expression and NO production. The phosphorylation of JNK and ERK1/2 was found to be necessary for NO production. Each phosphorylation pathway was found to require a Toll-like receptor (TLR) 4 as a prerequisite for PEP 1b-induced NO production. This study suggests that PEP 1b is an immunomodulatory protein that can boost cellular immune responses through the activation of the TLR4-NF-κB and MAPK signaling pathways.